A dynamic model of proliferation and differentiation in the intestinal crypt based on a hypothetical intraepithelial growth factor - Gerike, T. G. (Cell Prolif, 2003)
A widely accepted model of the temporal and spatial organization of proliferation and differentiation in intestinal epithelia is based on a cellular pedigree with all cells descending from a few active stem cells and undergoing a sequence of transitory divisions until the non‐proliferating maturing cell stages develop. Model simulations have shown that such a pedigree concept can explain a large variety of data. However, so far there is neither a direct experimental proof for the existence of an intrinsic age structure in the transitory proliferative cell stages nor for the distinction between stem and transitory cells. It is our objective to suggest an alternative model which is based on evidence for intercellular communications such as might be mediated through gap junctions. We consider the diffusion of a hypothetical intraepithelial growth factor in a chain of cells which are connected via gap junctions. Individual cells can divide if a critical growth factor concentration is exceeded. Simulation studies show that the model is consistent with many observed features of the small intestinal crypt in steady state and after perturbation.